Effect of electromagnetic field on abortion: A systematic review and meta-analysis - Ghazanfarpour Masumeh (De Gruyter, 2021)
The increasing use of new technologies by pregnant women inevitably exposes them to the risks of the electromagnetic fields (EMFs). According to the World Health Organization, EMFs are the major sources of pollutants which harm human health. This study was aimed to evaluate the effects of EMF exposure on abortion.